(untitled) (International journal of artificial intelligence, 2026)
This research addresses the critical challenge of resource management in small enterprises. Unlike large corporations, small businesses operate under severe budgetary and material constraints. This paper develops a linear programming model to maximize profitability by optimizing the distribution of limited labor and raw materials. By applying the Simplex method to a practical case study, the results demonstrate a potential increase in operational efficiency, proving that mathematical precision is superior to intuitive management.